Foreword From Editor - 16th Edition: Toward an Inclusive Community Engagement - Yatmo, Yandi Andri (UI Scholars Hub, 2024)
This edition of AJCE defines and elaborates on the idea of inclusive community engagement as a means to involve the community in a meaningful process. ‘Inclusive’ refers to the principles of encompassing everyone, all individuals and groups alike, regardless of their identity, background, characteristics, needs, and perspectives, thereby ensuring that all voices are represented (Hodkinson, 2011). This practice extends beyond individuals with disabilities and embodies broader ideas of equality. Inclusive engagement plays a crucial part in fostering a constructive dialog that incorporates diverse perspectives within a community. Such engagements prioritize community participation in the decision-making process that affects their well-being (Chen & Stoddart, 2024). There is a growing emphasis on inclusive community engagement, as the current practices are often perceived as obsolete activities, non-inclusive, and failing to promote equity or authentic outcomes (Anthony, 2023). Often, community members who should be involved in the engagement process are excluded, despite the need to integrate with community life (Ohmer et al., 2022). Consequently, there is a need to shift community development approaches to better address local needs and interests, encouraging diverse and active forms of engagement (Chen & Stoddart, 2024; Ohmer et al., 2022). Inclusive community engagement is crucial to prevent illusive interactions where only select stakeholders have a voice in decision-making (Anthony, 2023). By fostering inclusive engagement, communities can gain valuable insights and resources, significantly enhancing their livelihood and building a stronger and more resilient community. The shift toward more inclusive empowerment requires an understanding of community as an evolving idea. It is essential to view the community not merely as a homogenous entity defined by specific locations and a shared identity, such as the Indigenous and rural communities, but as a collective that consists of diverse ideas with fluid and ambiguous boundaries (Chen & Stoddart, 2024; Dempsey, 2010). A community can be also an imagined one, tied with culturally shared values that extend beyond mere physical geography. Additionally, communities can also be shaped by the social-relational networks that dynamically pursue global collaboration, emphasizing access and interactions among individuals, groups, or institutions as stakeholders. The advancement of information and communication technology has enabled them to voice their concerns and priorities, thereby calling for innovative and creative approaches to community engagement (Head, 2007). By recognizing the community as a collective of individuals and groups to be engaged in the development process, a variety of perspectives, experiences, and valuable insights are taken into account.